Native mass spectrometry reveals the initial binding events of HIV-1 rev to RRE stem II RNA - Eva-Maria Schneeberger (Nature Portfolio, 2020)
The HIV-1 RNA-binding protein rev facilitates nuclear export of viral RNA. Here, the authors use native mass spectrometry to study the interactions between rev-derived peptides and rev response elements of HIV-1 RNA, providing mechanistic insights into rev recognition and recruitment.